A Postcolonial Perspective Of Salman Rushdie’s Midnight’s Children (Journal of Namibian Studies : History Politics Culture, 2023)
Writing transcends the real world because its creators are not limited by political agendas. Literature is a reflection of the ideological and cultural factors that shape the historical and cultural setting of the literary work. Indian-born British author Salman Rushdie focuses on the numerous links, rifts, and migrations between Eastern and Western civilizations in his works of historical fiction mixed with magical realism. A large portion of Rushdie’s literature is set in the Indian subcontinent. In Rushdie’s works, the nation’s history is told and revealed via a single character’s life. According to Rushdie, human history is like a continuous text that incorporates both historical and modern elements. The argument that Rushdie, like other postcolonial writers, appears to be looking for new social structures and realities is discussed in this essay. He argues in Midnight’s Children that the world is complicated and hybrid, with entwined shared relations. To shift from the conventional notions of national identification to cultural identity, one must reject the nation, religion, and convention as determining factors.